2021
DOI: 10.21037/jgo-20-332
|View full text |Cite
|
Sign up to set email alerts
|

ALBI grade in dialysis patients with hepatocellular carcinoma: prognostic impact and staging strategy

Abstract: Background: Patients with hepatocellular carcinoma (HCC) may develop end-stage renal disease and receive dialysis, but the impact of dialysis on the prognosis is unclear. This study aimed to evaluate the outcome of dialysis HCC patients and the prognostic role of albumin-bilirubin (ALBI) grade in these patients. Methods: Among the consecutive 3,794 HCC patients between 2002-2017, 43 patients undergoing dialysis, and 129 age, sex-matched controls were analyzed. Multivariate Cox hazards model was used to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Hsu et al ( 13 ) reported that CKD could result in a poor outcome of patients who underwent TACE. Another study did propensity score matching (PSM) and found that the CKD group had poor prognosis, ( 23 ) the baseline information had no significant difference after the PSM, and more studies with the PSM method were needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al ( 13 ) reported that CKD could result in a poor outcome of patients who underwent TACE. Another study did propensity score matching (PSM) and found that the CKD group had poor prognosis, ( 23 ) the baseline information had no significant difference after the PSM, and more studies with the PSM method were needed in the future.…”
Section: Discussionmentioning
confidence: 99%